An empirical inquiry into the determinants of public education spending in Europe - Catalin Dragomirescu-Gaina (IZA Journal of European Labor Studies, 2015)
This paper makes two important contributions. Firstly, it uncovers some of the main economic determinants driving the dynamics of public education spending in Europe. Drawing mainly on the insights provided by Baumol's cost theory, the baseline specification uses unit labour costs and real GDP per capita as its main determinants. Some important institutional rigidities are also highlighted. The results confirm the fast relative increase in education costs, exposing the long-term affordability challenge of public education investment. Secondly, by including a policy objective and translating the empirical specification into a decision rule, the paper touches on some less mentioned determinants, such as policy commitment. Unfortunately, there is only weak overall evidence that public education spending would increase in response to a lack of progress in the policy objective. Finally, policy implications are discussed.
Keywords: D78; H41; H52; I22; 330; Education spending; Baumol cost disease; Policy commitment